A case of esophageal ulcer and hemorrhage due to aberrant subclavian in a COVID positive patient. Issue 1 (26th January 2022) - Hlayhel, Ahmad; Foran, Lindsey; Trivedi, Aakash; Zuberi, Jamshed; Cerda, Luis; Danks, John
Abstract: Coronavirus Disease 2019 (COVID-19), a global pandemic, is a respiratory infection that impairs the lungs among many other organs. We report a case of a COVID-19 positive patient requiring prolonged mechanical ventilation with nasogastric tube for enteral feeding, leading to esophageal ulcer and hemorrhage, from an aberrant right subclavian artery.